2019
DOI: 10.1101/697474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mozambican genetic variation provides new insights into the Bantu expansion

Abstract: The Bantu expansion, which started in West Central Africa around 5,000 BP, constitutes a major migratory movement involving the joint spread of peoples and languages across sub-Saharan Africa. Despite the rich linguistic and archaeological evidence available, the genetic relationships between different Bantu-speaking populations and the migratory routes they followed during various phases of the expansion remain poorly understood. Here, we analyze the genetic profiles of southwestern and southeastern Bantu-spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…It started in west‐central Africa 5,000–3,000 years ago, and evolutionary genetics demonstrated that mass human migration was the main underlying force of this expansion . New cross‐disciplinary research projects will elucidate long‐distant spread of farming practices and the interaction of migrating farmers with autochthonous groups, to shed additional light of when, where, and how early Bantu‐speaking populations settled in wider regions from central, eastern, and southern Africa …”
Section: New Insights To Study Past and Recent History In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…It started in west‐central Africa 5,000–3,000 years ago, and evolutionary genetics demonstrated that mass human migration was the main underlying force of this expansion . New cross‐disciplinary research projects will elucidate long‐distant spread of farming practices and the interaction of migrating farmers with autochthonous groups, to shed additional light of when, where, and how early Bantu‐speaking populations settled in wider regions from central, eastern, and southern Africa …”
Section: New Insights To Study Past and Recent History In Africamentioning
confidence: 99%
“…20 It started in westcentral Africa 5,000-3,000 years ago, and evolutionary genetics demonstrated that mass human migration was the main underlying force of this expansion. 21,22 New cross-disciplinary research projects 23 On both sides of the African continent, recent mass migrations contributed to one of the humanity's darkest chapters, the slave trade.…”
Section: New Insights To Study Past and Recent History In Africamentioning
confidence: 99%